The Role Of Brand Attachment In Mediating Usability And Information Quality On Brand Loyalty In Traveloka E-Commerce - wulandari, Ananda eri; Komariyatin, Nurul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Study this is to examine the role of brand attachment as a mediator in the relationship between usability and information quality, and its influence on brand loyalty within the context of Traveloka as an e-commerce platform. The research employs a quantitative approach, utilizing data collected through online questionnaires administered to 150 respondents. Hypothesis testing is conducted using SmartPLS version 4.0 as a data analysis tool. The findings indicate that both usability and information quality of the platform exert a positive influence on brand attachment, which subsequently enhances brand loyalty.